Covalently immobilized triphenylphosphine rhodium complex: synthesis, characterization, and application in catalytic olefin hydrogenation - Wang, Lei; Jia, Mingjun; Shylesh, Sankaranarayanapillai; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Singh, Anand Pal; Thiel, Werner R. (Chemcatchem, 2010)
A trimethoxysilane functionalized triphenylphosphine was coordinated to rhodium(I) and the resulting rhodium complex was covalently bound to a mesoporous SBA-15 support. The catalytic activity of this hybrid material was studied for the hydrogenation of 2-cyclohexen-1-one and compared with the corresponding homogeneous catalyst. According to the (31)P-MAS NMR data, the catalytically active species was stable against oxidation; no structural change could be detected after exposing it to air for more than two months. Transmission electron microscopy (TEM) measurements on the used catalyst confirmed that the rhodium species was also stable against reduction to the metal because the formation of rhodium nanoparticles during the catalysis could be excluded. The kinetic curves of the recycled system confirmed that this hybrid catalyst shows excellent activity, selectivity, stability, and reusability, and is truly heterogeneous in the hydrogenation reaction.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; mesoporous materials; Rhodium

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine